2016
DOI: 10.1080/14697688.2015.1114661
|View full text |Cite
|
Sign up to set email alerts
|

Dependence calibration and portfolio fit with factor-based subordinators

Abstract: The paper explores the properties of a class of multivariate Lévy processes, used for asset returns, with a focus on describing in an economic sensible and empirically appropriate way both linear and nonlinear dependence. The processes are subordinated Brownian motions. The subordinator has a common and an idiosyncratic component, to reflect the properties of trade, which it represents. A calibration to a portfolio of ten US stock indices returns over the period 2009-2013 shows that the hyperbolic specificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 27 publications
6
48
0
Order By: Relevance
“…The correlation flexibility of these models has been studied in the historical setting by Luciano et al (2016) and in the risk neutral one by Marena et al (2015). In both cases they provide an overall good performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation flexibility of these models has been studied in the historical setting by Luciano et al (2016) and in the risk neutral one by Marena et al (2015). In both cases they provide an overall good performance.…”
Section: Introductionmentioning
confidence: 99%
“…These classes of models have two di↵erent sets of parameters: idiosyncratic parameters, i.e., stock-specific, and common ones. Marginal distributions do not depend on common parameters, which are usually used to fit the correlation structure, see, e.g., Luciano and Semeraro (2010), Guillaume (2012) and Luciano et al (2016). This structure allows us to perform a satisfactory calibration of the marginal processes and, for given pairs of marginal parameters, to compare the correlation range allowed by the ⇢↵-Sato process with the correlation range allowed by their Lévy counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…Luciano and Schoutens [27] modeled the S&P500, the Nikkei225 and the Eurostoxx50 financial indexes by the variancegamma process. Luciano et al [29] and Wallmeier and Diethelm [43] confirmed the using of variance-gamma distribution for the modeling of the US and the Swiss stock markets, respectively.…”
Section: Introductionmentioning
confidence: 86%
“…The result of Theorem 1 follows from (34), where the functions DC(n 1 , n 2 , n 3 ) are computed with respect to (30) using (7) and (32) where I is defined in (29) and computed by (32)…”
Section: Proofsmentioning
confidence: 99%
“…Among others, let us mention the papers by Daal and Madan (2005), Finlay and Seneta (2006), Linders and Stassen (2016), Luciano et al (2016), Luciano and Schoutens (2006), Moosbrucker (2006), Mozumder et al (2015), Rathgeber et al (2016), and Wallmeier and Diethelm (2012), where the variance-gamma distribution is confirmed as a very good model to make out the statistics. For approximations of processes by the variance-gamma one, see Eichelsbacher and Thäle (2015).…”
Section: Introductionmentioning
confidence: 99%